Freedom Freedom to Learn: A Progressivism View and its Relevance to Teachers as Agent of Change (EFL Education Journal, 2023)
The purpose of writing is to analyze Independent Learning from the perspective of progressivism in educational reform, and its relevance for teachers as agents of change. Method of writing with literature review (library review). The literature review is carried out by collecting data from various library sources as a source of ideas to explore new ideas. Writing results: (1). Freedom to learn as an effort towards quality education, creating innovative and fun education, building superior, intelligent, creative human resources to face future challenges; (2). The concept of independent learning has parallels with the concept of progressivism emphasizing independence and flexibility for teachers, students, schools towards the implementation of education towards a better direction; (3). Freedom to learn in the perspective of progressivism has relevance to the teacher as an agent of change. Conclusion: Agent of change for teachers, implies that teachers are very influential in educational reform. Changing himself to act professionally, encouraging students to always progress as a generation that will respond to the challenges of changing times, in line with the goal of independent learning in the perspective of progressivism.